MI1 – derivative of maleimide inhibits cell cycle progression in tumor cells of epithelial origin - Garmanchuk, L.V.; Denis, E.O.; Nikulina, V.V.; Dzhus, O.I.; Skachkova, O.V.; Ribalchenko, V.K.; Ostapchenko, L.I. (Вiopolymers and Cell, 2013)
Aim. MI1 is a promising maleimide derivative, which exhibits antiproliferative effect on different cells. The aim of present study was to investigate influence of MI1 on the cell cycle of cancer cells and its cytotoxity. Methods. The proliferative activity and viability of human cancer cell lines (colorectal adenocarcinoma – Colo-205; breast cancer – MCF-7; cervix cancer HeLa) obtained with MTT-test and cell counts were performed using a tripan blue dye. Distribution of cell cycle phases was obtained using flow cytometry method. Results. In the present study we demonstrate a detectable cytostatic effect of the maleimide derivative MI1 on the epithelial cell lines Colo-205, MCF-7 and HeLa. In the presence of MI1 the number of cells in the G2/M+S phases of the cell cycle dropped by 20–30 % (p < 0.05) relative to control. Conclusions. The results suggest that MI1 may be a perspective drug for antitumor therapy and perhaps deserves further study in detail.